The Social issue and the favela: State violence, pandemic, and working-class organization - Santos, Francine Helfreich Coutinho dos; Farage, Eblin; Pinto, Marina Barbosa (Argumentum, 2020)
Abstract: This text discusses daily life in the favelas, which is marked by State violence that, in the context of the Covid-19 pandemic, reiterates its class character. These are places where the destabilizing actions of the State are expressed - regarding social demands – while simultaneously imposing the presence of its armed forces under the rhetoric of maintaining order and controlling violence. The textpresents the historic construction of the favelas in Rio de Janeiro; the everyday discussions, colored by the political presence of the State for “in”security; and some elements around the forms of resistance built by the working class sectors that live in the favelas. The methodology used is expressed along three axes: exploratory research to reach the proposed objectives, bibliographic review dialoguing with classic and contemporary authors, and qualitative research.Keywords: Favela. Pandemic. Workers’ organization.